Effect of total lysine:crude protein ratio on growth performance of nursery pigs from 15 to 25 lb - J E Nemechek; J Usry; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 282 nursery pigs (PIC TR4 × 1050, initially 15.9 ± 0.15 lb BW and 3 d postweaning) were used in a 28-d growth trial to evaluate the effects of total lysine:CP ratio, using fish meal as a source of non-essential N, on growth performance. Pigs were allotted to 1 of 6 dietary treatments. Each treatment had 5 replications with 7 pigs per pen and 2 replications with 6 pigs per pen. Pigs and feeders were weighed on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. A 2-phase diet series was used with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. All diets were in meal form. The 6 total lysine:CP ratios were 6.79, 6.92, 7.06, 7.20, 7.35, and 7.51%. From d 0 to 14, there was a trend for increased (quadratic; P<0.09) ADG with an increasing dietary total lysine:CP ratio up to 7.35%, with poorer performance in pigs fed the greatest lysine:CP diet. Increasing the total lysine:CP ratio tended to improve (quadratic; P<0.09) F/G for pigs fed 7.35%, with poorer F/G as total lysine:CP ratio increased to 7.51%. When a common diet was fed (d 14 to 28), there was no difference in ADG or F/G. A response (quadratic; P<0.04) was detected for ADFI due to an increase in ADFI from the pigs fed the intermediate diets (7.06 and 7.20% total lysine:CP) during the previous period. Overall (d 0 to 28), there was a trend (quadratic; P<0.07) for increased ADG and ADFI caused by the numerically highest values from pigs fed a total lysine:CP ratio of 7.35% and the numerically lowest values from pigs fed a total lysine:CP ratio of 7.51%. Dietary treatment did not influence F/G for the overall trial. These results indicated that feeding total lysine:CP ratio greater than 7.35% may decrease growth performance of nursery pigs.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Fish meal; Lysine; Nonessential amino acids; Nursery pig